Gluten hyper sensitivity: an unseen storm of neurological spectrum disorders - Chaudhary, Ansh; Chaudhary, Bhupendra (International Journal of Advances in Medicine, 2020)
Gluten sensitivity, an autoimmune systemic disease with its protean manifestation occur in genetically susceptible individuals with gluten in their diet. Coeliac disease is the intestinal form of disease mostly seen in children with predominant gastrointestinal manifestations. The neurological presentation of gluten sensitivity mostly without enteropathy are also frequent and affect adult population in contrast. The most common presentation includes cerebellar ataxia, peripheral neuropathy and seizure followed by encephalopathy, schizoaffective and movement related manifestations. These varied clinical presentations are attributed to an immune related attack on central and peripheral nervous system involving both adaptive and innate immunity. Early suspicion, prompt diagnosis and institution of gluten free diet provides remarkable benefits to these patients with amelioration of troublesome symptoms. A better understanding of disease etiopathogenesis is likely to add more therapeutic options.